PERNYATAAN WAKTU BERBENTUK FRASA DALAM BAHASA BUGIS (Deictic Phrase in Buginese Language) - syamsul_rijal Aziz (Balai Bahasa Sulawesi Selatan, 2018)
The purpose of this research is to describe deictic phrase in Buginese language. The method used is descriptive method by using notive and constituend recording technique. In addition, documentation analysis of some texts of Buginese research and literary was also conducted. The theory used in data analysis is structural linguistic theory. The result show that deictic phrase Buginese language have constitued based on the type of construction, namely endocentric phrase and exocentric phrase. Both have different components or constituens, either in the relationship of its constituens element or of its syntactic behavior Keywords: sintax, deictic, endocentric and exocentric phrase, Buginese language